Evaluasi Program Penanggulangan Penyakit Diabetes Mellitus di Kota Bukittinggi Provinsi Sumatera Barat Tahun 2025 - Yunita Diastanti; Eka Budi Satria; Masrizal (3031-8572, 2025)
Diabetes Mellitus is a major non-communicable disease and remains a significant public health issue in Indonesia, including in Bukittinggi City. Situation analysis in 2022 and health problem review in 2024 showed that DM consistently ranks within the top five health priorities in this region. Health Office reports indicate increasing DM cases from 2022 to 2024, while the Minimum Service Standards achievement exceeded 100%. This suggests that administrative achievement does not fully reflect effective program implementation. This study aimed to evaluate the implementation of the DM control program in Bukittinggi City. A descriptive evaluation was conducted through structured interviews with 12 program officers from the Health Office and community health centers. The assessment covered four evaluation components: input, process, output, and outcome. Results showed that the program generally followed national guidelines but encountered several challenges. For input, human resources, facilities (63.6%), and funding (54.5%) were considered adequate; however, most officers had not received specific DM training (81.8%) and still had multiple responsibilities (66.7%). Regarding process, early detection, education, and monitoring activities were implemented, yet planning involvement remained limited (72.7%). At the output level, core activities were running, but some health centers had not conducted DM surveillance or developed community referrals (28.6%). Regarding outcomes, the program contributed to improved patient quality of life (54.5%), although community participation was still low. Strengthening the program is expected through improved staff capacity and proportional task assignment, greater involvement in planning, strengthened surveillance and community networks, and increased community participation through education.